COMMUNICATION OF PUBLIC POLICY IN IMPLEMENTING KAMPUNG TEMATIK PROGRAM IN REJOMULYO SUB-DISTRICT OF SEMARANG - Reina Hapsari Ayuningtyas; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2020)
ABSTRACT Regulation of Thematic Village program was formed to deal with poverty in the city of Semarang, but there are some problems related to communication interwoven among stakeholders in this implementation. This research aims to analyze the communication between stakeholders in implementing the policy of thematic village program in the Rejomulyo Semarang, This research will focused on Stakeholders Communication and implementation of the thematic village program in Rejomulyo Semarang. The method of research used is a qualitative descriptive approach with purposive sampling informant determination technique. The results of the study showed, communication conducted by the Government of Semarang in the form of socialization of thematic village planning followed by representatives of all kelurahan and sub-districts in Semarang, workshops and FGD, while PT PLN did direct communication by discussion on the CSR that will be implemented in Kampung Batik Rejomulyo village. Then the Polines academics is to offer assistance to the Chairman RW 002 by means of door to door and coordination meeting attended by some residents and local community figures. But in the implementation there are some obstacles include: the uncertainty of communication done by one of stakeholders in communicating the assistance that will be given to residents of Batik village that raises mis-interpretation, Then there was inconnection between the government and academics. Advice that can be given by researchers is: it is necessary to increase awareness between stakeholders in the cooperation of intensive communication between stakeholders in order to minimize understanding of the communication Performed by the stakeholders.